Study on the Characteristics of Schottky Temperature Detector Based on Metal/n-ZnO/n-Si Structures - Wang, Fang; Wei, Jingkai; Guo, Caixia; Ma, Tao; Zhang, Linqing; Xia, Congxin; Liu, Yufang (Micro and Nanosystems, 2021)
Background: At present, the main problems of Micro-Electro-Mechanical Systems (MEMS) based temperature detector are the narrow range of temperature detection and difficulty in the measurement of high temperature. Besides, MEMS devices have different response characteristics for various surrounding temperature in the petrochemical and metallurgy application fields with hightemperature and harsh conditions. To evaluate the performance stability of the high-temperature MEMS devices, the real-time temperature measurement is necessary. Objective: A Schottky temperature detector based on the metal/n-ZnO/n-Si structures is designed to measure high temperature (523∼873K) for MEMS devices with a large temperature range. Methods: By using the Finite Element Method (FEM), three different work function metals (Cu, Ni and Pt) contacting the n-ZnO were investigated to realize Schottky. At room temperature (298K) and high temperature (523∼873K), the current densities with various bias voltages (J-V) were studied. Results: The simulation results show that the high-temperature response power consumption of three Schottky detectors of Cu, Ni and Pt decreases successively, which is 1.16 mW, 63.63 μW and 0.14 μW. The response temperature sensitivities of 6.35 μA/K, 0.78 μA/K, and 2.29 nA/K are achieved. Conclusion: The Cu/n-ZnO/n-Si Schottky structure could be used as a high-temperature detector (523∼873K) for the high-temperature MEMS devices. It has a large temperature range (350K) and a high response sensitivity of 6.35 μA/K. Compared with the traditional devices, the Cu/n-ZnO/n-Si Schottky structure-based temperature detector has a low energy consumption of 1.16 mW, having potential applications in the high-temperature measurement of the MEMS devices.
Keywords: Schottky structure